Graphene-based implantable neural electrodes for insect flight control. Issue 24 (1st June 2022) - Xiong, Jian; Zhang, Bin; Balilonda, Andrew; Yang, Shengyuan; Li, Kerui; Zhang, Qinghong; Li, Yaogang; Wang, Hongzhi; Hou, Chengyi
Abstract : Implantable PEDOT:PSS/graphene neural electrodes with enhanced charge storage capacity show good performance in insect flight control experiments. Abstract : Implantable neural electrodes have been widely used to investigate the function of the brain and treat neurological disorders. Due to their advantages of size and preparation, fibrous neural electrodes have been widely applied, but conventional metal wire electrodes have many shortcomings that are impossible to overcome. Here, we present a modified graphene-based fiber electrode, which retains the excellent electrical properties of the graphene fiber (GF) electrode and enhances the charge storage capacity (CSC) from the initial 7.97 mC cm −2 to 504.04 mC cm −2 . The modified electrodes were further investigated via in vivo experiments, and the results show that the modified graphene fibers controlled insect flight with a minimum voltage close to that of silver wire electrodes, and no irreversible chemical reaction occurred during the electrical stimulation process, which could achieve the stimulation effect while ensuring the safety of the tissues around the electrodes.